The Role of Chief Executive Officer Leadership in Institutionalizing Corporate Social Responsibility in Twenty Sustainability-Driven British and American Companies - Prashanth, Manoj Appuswamy (2008)
Corporate Social Responsibility (CSR) is fundamentally a vision about the relationship of business and society that requires leadership to inspire, implement and sustain it over a period of time (World Business Council for Sustainable Development, 2008). This study identified all the contemporarily evolving styles of CSR leadership in the field of management today, both from the length of corporate information and from the breath of academic literature, and has finally settled down with seven major styles of leadership that were found to be effectively contributing to the understanding, implementation and propagation of CSR. Focusing on the leadership impetus provided by the Chief Executive Officers (CEOs) towards the promotion of CSR in their firms balanced with the economics of the firm, the study involves 20 multinational companies that have already benchmarked themselves in the area of CSR selected from the United Kingdom (UK) and the United States of America (USA). However, this study has not ignored the established theories of leadership that are believed to be the original frameworks of thought for the emerging styles of CSR leadership. It uses two major theories, namely the transformational leadership and transactional leadership, and finally groups the CSR-based leadership styles into one of the functional group, either transformational or transactional. A transactional approach is always preferred because businesses need to rationalise their need for engaging themselves in any socially responsible activity that is not core to their business or not stipulated by the law of the land where they operate. The study is not empirical in nature, but uses authentic information from the CSR reports published annually by companies. It bases its analysis of CEO-CSR leadership on the forewords given by CEOs in the CSR reports, also analysing the comprehensiveness of those messages.